Factors influencing family member perspectives on safety in the intensive care unit: a systematic review. (9th September 2020) - Coombs, M A; Statton, S; Endacott, C V; Endacott, R
Abstract: Purpose: Patient safety has developed as a strong marker for healthcare quality. Safety matters are important in the intensive care unit (ICU) where complex clinical decisions are made, intensive technology is used, and families hold a unique role. The aim of this review was to identify and describe factors that influence family member's perceptions of safety in the adult ICU. Data sources: Searches were conducted between September and November 2018 and repeated in July 2020 using CINAHL, MEDLINE (EBSCO), PubMed and PsycINFO databases. Study selection: Published primary studies undertaken in adult ICUs and involving adult family member participants exploring safety or feeling safe. No date restrictions were applied. Data extraction: A data extraction form collected information about sample, study design, data collection methods and results from each paper. Methodological quality was assessed using the QualSyst tools for qualitative and quantitative studies. Narrative synthesis was undertaken. Results of data synthesis: Twenty papers were included with 11 papers published since 2010. The majority of papers reported on qualitative studies (n = 16). Four factors were identified that influenced whether family members felt that the patient was safe in ICU: family visiting, information and communication, caring and professional competence. Conclusion: In detailing specific practices that make families feel safe and unsafe in ICU, these review findings provide a structure for clinicians, educators and researchers to inform future work and gives opportunity for the family role in patient safety to be reconsidered.